Influences of Draw Forming Process on the Crash Analysis of a Circular Cup - Amman, R.M.; Halim, M.F.; Sivakumar, D.; Abu-Shah, I.; Sulaiman, S.N.; Samekto, H.; Subramonian, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The change of a structural part that occurred after forming process can affect crash response. Current industrial practice only utilizes the geometry in crash analysis. This study investigates the effect of forming histories of a circular cup formed by draw forming process in the crash simulation. Crash analysis at an initial velocity of 50km/h was performed using the explicit finite element code Radioss. The Johnson-Cook constitutive material model was used to characterize the material properties of advanced high strength steel DP600. Crash simulations are conducted in two different cases using a geometrical cup model with case 1 no forming history and case 2 all forming histories obtained from forming process. Results from this study indicate that the mechanical response of steel DP600 in a crash differ by 80.7 % for contact force and 5.87% for energy absorption when forming effects were considered. The contact force tends to increase more with displacement in case 2 compared to case 1. The non-uniform thickness and work hardening from forming process do alter significantly the crashworthiness of a structural part in the subsequent crash event.